The Inhibitory Effects of Neem Oil against the Development of Plasmodium berghei in Mice (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Although neem oil extract is widely used in Africa and Asia for the treatment and prevention of malaria, its inhibitory effect on the growth of malaria parasites in vivo has not been fully tested. In the present study, the inhibitory effects of neem oil extract against the growth of rodent malaria parasite in the mice were investigated. The results revealed that administration of neem oil to the mice infected by rodent malaria parasite reduces the rate of development of Plasmodium berghei. These results show that neem oil extract could be an effective antimalarial agent in humans that merits further investigations using human parasites.
Keywords: Neem oil; inhibitory effect; Plasmodium berghei; mice